Investigation of Hydrogen Incorporations in Bulk Infinite-Layer Nickelates - Puphal, P.; Pomjakushin, V.; Ortiz, R. A.; Hammoud, S.; Isobe, M.; Keimer, B.; Hepting, M. (Frontiers in Physics, 2022)
Infinite-layer (IL) nickelates are an emerging class of superconductors, where the Ni$^{1+}$ valence state in a square planar NiO$_2$ coordination can only be reached via topotactic reduction of the perovskite phase. However, this topotactic soft chemistry with hydrogenous reagents is still at a stage of rapid development, and there is a number of open issues, especially considering the possibility of hydrogen incorporation. Here we study the time dependence of the topotactic transformation of LaNiO$_3$ to LaNiO$_2$ for powder samples with x-ray diffraction and gas extraction techniques. While the hydrogen content of the powder increases with time, neutron diffraction shows no negative scattering of hydrogen in the LaNiO$_2$ crystal lattice. The extra hydrogen appears to be confined to grain boundaries or secondary-phase precipitates. The average crystal structure, and possibly also the physical properties, of the primary LaNiO$_2$ phase are therefore not noticeably affected by hydrogen residues created by the topotactic transformation.